Problematika Penguasaan Kosa Kata Bahasa Arab Siswa Kelas IV di MI Salafiyah Kranggan - Faizah Faizah; Ayu Rahma Agustina; Eka Mahargiani Rokhma; Madya Dr Azlan Shaiful Baharum (At Turots: Jurnal Pendidikan Islam, 2025)
The purpose of this study was to analyze the problematic mastery of Arabic vocabulary of fourth grade students at MI Salafiyah Kranggan. The research method used is descriptive qualitative with samples of fourth grade Arabic teachers and fourth grade students, while the data is collected using unstructured interview techniques, documentation and non-participant observation. The results showed; 1) the problematic mastery of students' Arabic vocabulary was caused by several factors. Among them are factors originating from teachers who have not made maximum innovation in learning media, both the use of methods and learning media, besides that mastery of material that has not been maximized due to low reading references and pedagogical competence. Factors originating from students are evidenced by the low interest and motivation to learn Arabic due to the low reading material and teaching creativity in the classroom. Some other factors come from the lack of maximization of media facilities in madrasah and the family environment; 2) solutions that have been carried out by madrasah include; increasing Arabic reading references, innovating interesting learning processes, developing digital competencies of educators, increasing references to textbooks that are interesting to educators, upgrading them selves through several trainings for educators, and the regulation of Arabic teacher recruitment according to academic qualifications..